Fijne spot & milde satire in de hedendaagse kunst. - De Nys, Jan; Van der Eecken, Bea; De Wael, Marianne (Aalst : Kunstruimte Diskus, 2022)
Bernier, Pascal ; Bjarland, Sara ; Bragigand, Franck ; Charles, Michael Ray ; Copers, Leo ; Cutrone, Ronnie ; Dijkstra, Anno ; Droogh, Maurice ; Dubois, Joëlle ; Eckes, Sacha ; Feldmann, Hans-Peter ; Grootjans, Loek ; Haerizadeh, Rokni ; De Hoop, Harmen ; de Jong, Folkert ; Levine, Les ; Lampens, Carine ; Lutgens, William Ludwig ; Marty, Enrique ; Mat ; Mechnig, Karl ; Morrens, Peter ; De Nys, Jan ; Phlips, William ; Scoccimaro, Lionel ; Serrano, Andres ; Sevenans, Idris ; De Smedt, Jo ; Swennen, Walter ; Van den Block, Zena ; Van Dun, Jesse ; De Wit, Johan
Fijne spot & milde satire in de hedendaagse kunst, Kunstruimte Diskus, Aalst, 04/02 - 27/02/2022
boek